Multi-omics analysis reveals the dominant intestinal microbial strains and metabolites related to the reproductive performance in pregnant sows - Qianhong Ye; Tingting Luo; Longshan Han; Yuwen Chen; Yifan Hu; Haoyi Jiang; Xiaojian Xu; Xianghua Yan (Animal Nutriomics)
Gut microbiome changed dramatically during pregnancy and played important roles in metabolic status and reproductive endocrinology in mammals. However, investigating the functional microbiota and metabolites to improve the reproductive performance and understanding the host–microbiota interaction are still arduous tasks. This study aims to reveal the dominant strains and metabolites that improve the reproductive performance. We analyzed the fecal microbiota composition and metabolic status of higher yield Chinese pig breed Meishan (MS) sows and lower yield but widespread raised hybrid pig breed Landrace × Yorkshire (L × Y) sows on days 28 and 100 of gestation. Results showed that MS sows had higher litter sizes and steroid hormone level but lower short-chain fatty acid level in feces. Fecal metabolomic analysis revealed that MS sows showed a different metabolic status compared with L × Y sows both at early and late pregnancy, which enriched with phenylpropanoid biosynthesis, bile secretion, steroid hormone biosynthesis, and plant secondary metabolite biosynthesis. In addition, 16S rDNA and internal transcribed spacer sequencing indicated that MS sows showed different structures of microbiota community and exhibited an increased bacterial α-diversity but non-differential fungal α-diversity than L × Y sows. Moreover, we found that the litter sizes and bacteria including Sphaerochaeta, Solibacillus, Oscillospira, Escherichia–Shigella, Prevotellaceae_UCG-001, dgA-11_gut_group, and Bacteroides, as well as fungi including Penicillium, Fusarium, Microascus, Elutherascus, and Heydenia both have positive association to the significant metabolites at the early pregnancy. Our findings revealed significant correlation between reproductive performance and gut microbiome and provided microbial and metabolic perspective to improve litter sizes and steroid hormones of sows.